Energy expenditure at work in physical education teachers. (January 2015) - Trudeau, François; Laurencelle, Louis; Lajoie, Claude
Abstract: The objective of this study was to quantify work energy expenditure (EE) in physical education (PE) teachers. Sixty-four (64) physical educators (49 men, 15 women) had their individualized linear function between heart rate (HR) and oxygen consumption measured by laboratory testing. HR was then recorded on 2 different days at work to estimate EE, correlated with a diary of daily tasks. Average absolute EE was low-to-moderate (2.7 ± 1.4 to 4.6 ± 2.5 kcal·min −1 ) and low when expressed in relative values (15.3 ± 6.1% to 24.8 ± 7.6% of VO2 max). However, these physical educators often reached very high intensities (from 7.5 ± 7.9% to 23.8 ± 22.3% of work time at 100 bpm and more). PE teaching requires a light-to-moderate EE with more intense periods of physical activity. The variety of tasks performed (office work, supervision and monitoring, mixed participation and active participation) significantly influenced EE. Highlights: Energy expenditure (EE) was measured in physical educators during 2 workdays. Physical education teachers showed a high level of fitness level. Average EE was low-to-moderate (kcal min − 1 ) and low in relative values (% VO2 max). However, physical educators reached very high work intensities for significant periods. Physical educators should be prepared to perform tasks with different levels of EE.